2020
DOI: 10.1111/1750-3841.15006
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds extraction in enzymatic macerations of grape skins identified as low‐level extractable total anthocyanin content

Abstract: Anthocyanins in wine principally depend on grape skin extractable anthocyanin content, that is, the amount of anthocyanins present in grape skin that are released to wine during the maceration stage. This amount of extractable anthocyanins is closely linked to the cell wall degradation of skin cells. Indeed, among other methodologies, the maceration in presence of different enzymes can be used to increase cell wall degradation, and therefore, the amount of anthocyanins extracted from grape skins to wine. Vitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The top-performing strains, demonstrating a lower capacity to adsorb polyphenols, were selected and characterized throughout the various phases of the study. It is known from the literature that yeast's enzymes (pectinase and glycosidases) may affect polyphenolic extraction, modifying the chemical structure of glycosylated phenolic molecules [38]. Moreover, polyphenols interact with yeast by binding to cell wall mannoprotein [9].…”
Section: Discussionmentioning
confidence: 99%
“…The top-performing strains, demonstrating a lower capacity to adsorb polyphenols, were selected and characterized throughout the various phases of the study. It is known from the literature that yeast's enzymes (pectinase and glycosidases) may affect polyphenolic extraction, modifying the chemical structure of glycosylated phenolic molecules [38]. Moreover, polyphenols interact with yeast by binding to cell wall mannoprotein [9].…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasonic energy for intensification and yields improvement of the anthocyanins' extraction were described by Ravanfar et al [113]. Anthocyanins extraction based on enzymatic maceration from the grape skin is also described as an environment-friendly technique [114]. In another report, effects of co-pigmentation on stability and extraction of anthocyanins has been described which suggested the use of certain organic acids to provide the stability of the anthocyanins-co-pigmented with organic acids, to be stable for about 2 months at 10 • C storage [115].…”
Section: Anthocyanins Quality and Contents' Control Through Spectro-a...mentioning
confidence: 99%
“…Zhang et al (2020) [36] showed that enzymatic extraction provided a more desirable profile of phenolic compounds with greater antioxidant activity, compared to other methods. According to Nogale-Bueno et al (2020) [37] it is possible to obtain extracts with enzymatic extraction up to 120% more phenolic than those obtained by conventional methods, which shows that the application of this technology to products with a high phenolic content, such as Amazonian herbs, can be very interesting.…”
Section: 99%mentioning
confidence: 99%